Sebuah APLIKASI VIRTUAL TOUR PENJUALAN PERUMAHAN BERBASIS AUGMENTED REALITY - Ivan Rochman; Anang Kukuh Adisusilo (Informatics Department-Universitas Wijaya Kusuma Surabaya, 2021)
The era after this pandemic requires property developers to apply industrial property technology that can survive in the midst of social restrictions and physical distancing, which also has an impact on sales. How to use technology as a medium for increasing sales, so that consumers can see residential buildings presented interactively, with that information about buildings can be known including the room in a house building. The Augmented Reality-Based Virtual Tour Application for Housing Sales is an application that is a construction design and helps provide and present information about the initial prototype of the housing design that will be sold. This housing design is accompanied by supporting data that is useful for presenting the information needed from the area, type, and specifications of housing presented with augmented reality-based virtual tour technology as if it were original with a real form. The results show that it can help increase sales, in which there is augmented reality technology and virtual tours that present interesting information.